Editorial: Harnessing marine biodiversity for novel antimicrobial agents against multidrug-resistant pathogens - Agüero-Chapin, Guillermin; Domínguez-Pérez, Dany; Marrero Ponce, Yovani (Frontiers Media SA, 2025)
Antimicrobial resistance (AMR) is a defining challenge of our era, responsible for an alarming number of deaths that now surpass those caused by HIV and malaria. Projections estimate that by 2050, AMR could lead to 10 million deaths annually. The COVID19 pandemic has amplified this crisis, fueling the spread of multidrug-resistant (MDR) pathogens, particularly those associated with biofilms. In response, governments have begun adopting more agile investment models, while academia and emerging biotech initiatives play increasingly central roles in the discovery of next-generation antimicrobials. The ocean, covering over 70% of Earth’s surface, represents an extraordinary yet underexploited reservoir of chemical diversity. Marine ecosystems harbor a vast array of microorganisms and multicellular life forms adapted to extreme and varied habitats. These organisms, from actinomycetes to fish and fungi, produce structurally unique secondary metabolites as chemical defenses or communication tools—many of which exhibit promising antimicrobial activities. This Research Topic aims to showcase the potential of marine biodiversity in providing new solutions to counteract MDR pathogens. © The authors © Frontiers Media.
Keywords: Multidrug resistance; Marine antimicrobials; Bioassays; Screening techniques; Drug discovery